Online Liquid Microextraction Coupled with HPLC-ABTS for Rapid Screening of Natural Antioxidants: Case Study of Three Different Teas. (13th August 2020) - Qian, Zheng-Ming; Fang, Bo-Wen; Chen, Hai-Ming; Li, Chun-Hong; Huang, Qi; Chen, Ling; Li, Wen-Jia; Li, De-qiang
Abstract: In the present study, an online liquid extraction coupled with high-performance liquid chromatography-2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (HPLC-ABTS) system for rapid screening of antioxidants in tea samples was proposed. As an example, the tea samples were firstly extracted by online HPLC extractor with mobile phase at 70°C, then the hyphenated HPLC-ABTS was used for the chromatographic separation on a Poroshell EC C18 column by 0.3% aqueous formic acid and acetonitrile with a gradient elution at 1.5 mL·min −1, and the UV and antioxidant chromatograms with detection wavelengths at 270 nm and 750 nm were recorded, respectively. The established system integrated the processes of online HPLC sample extraction, HPLC separation and online antioxidants detection, the total analysis time of which was <20 min. The developed method was successfully applied to samples of green tea, oolong tea and black tea. As a result, 11 antioxidants were found in tea samples, including gallocatechin, epigallocatechin, catechin, chlorogenic acid, epicatechin, epigallocatechingallate, epicatechingallate, rutin, 1, 4, 6-trigalloylglucose, quercetin-3-glycoside and kaempferol-3-glucoside. The combined online liquid microextraction and online HPLC-ABTS method is a rapid and green approach for the quality evaluation of tea.